Pemberdayaan Masyarakat Pondok Pesantren (Santriwati) dalam Pembuatan Sabun Cuci Pakaian Berbahan Dasar Minyak Jelantah - Novi Rahmawanti; Novrian Dony; Andita Novriwanti (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Waste cooking oil/used cooking oil which is blackish brown is residue from the frying process that still contains fatty acids which have the potential to be used to make soap.  At the Al Ihsan Puteri Islamic boarding school, Banjarmasin used cooking oil waste has not been managed well. This activity aims to educate the Islamic boarding school community (santriwati) and boarding school administrators about making washing soap from used cooking oil as a solution so that used cooking oil can be reused in other forms. Participants in the activity were 15 female students at the Al Ihsan Puteri Banjarmasin Islamic Boarding School. This activity consists of discussion (counseling) and direct practice. The chemistry knowledge education material explains the impact of used cooking oil on the body, while the soap-making training material explains the cold saponification method through demonstrations. The service results show that almost 100% of the students who initially did not know how to reuse used cooking oil in soap, now know how to reuse used cooking oil. Students also increase their knowledge and skills in reacting with materials in the saponification process.